Comparative Evaluation of HPMC, PVA and Gelatin as Matrices for Controlled Release Drug Delivery (Stamford Journal of Pharmaceutical Sciences, 2010)
The present study was undertaken to compare three different polymeric gums- HPMC, PVA and gelatin as controlled release matrices. Diclofenac sodium, a potent analgesic, was used as the model drug. Different ratio of HPMC, PVA and gelatin were incorporated into the lactose loaded Diclofenac tablet to explore their impact on drug release. Matrix tablets of Diclofenac were prepared by using individual polymer with magnesium stearate and aerosil by direct compression process at 5 ton pressure. The release of drug from these matrices was studied over 2 hrs in acidic media where insignificant release was observed. Then, the same formulations were studied over 8 hours in buffer media of pH 6.8 at a temperature of 37± 0.5°C. Statistically significant differences in drug release profile was found among the tablets prepared from different matrices. The study revealed that the average % release of drug from different types of polymer loaded matrix tablet varied with the ratio of different polymers. Among the three polymers, PVA showed best dissolution pattern. A comparison of Higuchi curve and bi-exponential curve was also performed. Key words: HPMC; PVA; Gelatin; Controlled release; Diclofenac DOI: 10.3329/sjps.v2i1.5816Stamford Journal of Pharmaceutical Sciences Vol.2(1) 2009: 51-55